Розсуд у кримінальному процесі України - Торбас, Олександр Олександрович; Торбас, Александр Александрович; Torbas, Oleksandr O. (My University, 2021)
Дисертація на здобуття наукового ступеня доктора юридичних наук за спеціальністю 12.00.09 – кримінальний процес та криміналістика; судова експертиза; оперативно-розшукова діяльність. – Національний університет «Одеська юридична академія», Одеса, 2021. Дисертація є першим у вітчизняній науці кримінального процесуального права спеціальним комплексним дослідженням реалізації розсуду в кримінальному процесі України відповідно до положень КПК України 2012 року. У дисертації визначено поняття, ознаки та види розсуду в кримінальному процесі. З’ясовано сутність меж розсуду та їх співвідношення з детермінантами розсуду в кримінальному процесі. Встановлено сутність та характерні особливості суддівського розсуду. Охарактеризовано процес застосування розсуду слідчим суддею під час досудового розслідування. Визначено особливості реалізації розсуду судом під час розгляду кримінального провадження в судах першої, апеляційної та касаційної інстанцій. Розкрито зміст та характерні ознаки розсуду, що реалізується прокурором у кримінальному провадженні. Встановлено особливості реалізації розсуду прокурором під час досудового розслідування. Охарактеризовано процес реалізації розсуду прокурором на судових стадіях кримінального провадження. Визначено сутність та ознаки розсуду слідчого та дізнавача. Розкрито характерні особливості застосування розсуду слідчим та дізнавачем під час розслідування кримінальних правопорушень. Розглянуто процес реалізації розсуду керівниками органу дізнання та досудового розслідування. Визначено порядок застосування розсуду співробітниками оперативних підрозділів та представниками персоналу органу пробації. Сформульовано теоретично обґрунтовані пропозиції щодо вдосконалення кримінального процесуального законодавства в частині реалізації розсуду уповноваженими суб’єктами кримінального провадження.

Диссертация на соискание научной степени доктора юридических наук по специальности 12.00.09 – уголовный процесс и криминалистика; судебная экспертиза; оперативно-розыскная деятельность. – Национальный университет «Одесская юридическая академия», Одесса, 2021. Диссертация является первым в отечественной науке уголовного процессуального права специальным комплексным исследованием реализации усмотрению в уголовном процессе Украины в соответствии с УПК Украины 2012 года. В диссертации определены понятие, признаки и виды усмотрения в уголовном процессе. Установлена сущность пределов усмотрения в уголовном процессе и их соотношение с детерминантами усмотрения в уголовном процессе. Раскрыта сущность и характерные особенности судейского усмотрения. Охарактеризован процесс применения усмотрения следственным судьей во время досудебного расследования. Определены особенности реализации усмотрения судом при рассмотрении уголовного производства в судах первой, апелляционной и кассационной инстанции. Раскрыто содержание и характерные признаки усмотрения, реализуемого прокурором в уголовном производстве. Установлены особенности реализации усмотрения прокурором во время досудебного расследования. Охарактеризован процесс реализации усмотрения прокурором на судебных стадиях уголовного производства. Определена сущность и признаки усмотрения следователя и дознавателя. Раскрыты характерные особенности применения усмотрения следователем и дознавателем при расследовании уголовных преступлений. Изучен процесс реализации усмотрения руководителями органа дознания и досудебного расследования. Определен порядок применения усмотрения сотрудниками оперативных подразделений и представителем персонала органа пробации. Сформулированы научно обоснованные предложения о внесении изменений и дополнений в УПК Украины для совершенствования процедуры реализации усмотрения в процессе расследования, рассмотрения и разрешения уголовных производств.

The dissertation for a degree of the Doctor of Law in a specialty 12.00.09 – Criminal Process and Criminalistics; Forensic Examination; Operational and Investigative Activities. – National University «Odessa Law Academy», Odesa, 2020. The dissertation is the first in the domestic science of criminal procedural law special complex research of essence and ways of realization of discretion in the criminal procedure of Ukraine according to the 2012 CPC of Ukraine. The dissertation establishes the concepts, features and types of discretion in criminal proceedings. It was established that discretion in criminal proceedings can be defined as the possibility of exercising powers of adopting one legally binding legal decision of several alternatives proposed by criminal procedure law with the use of intellectual-volitional mechanism in accordance with the circumstances of particular criminal proceeding, taking into account principles of criminal proceedings, professional experience of law enforcement, judicial and investigative practice, moral and ethical characteristics of law enforcement subject, in order to ensure private and public interests in criminal proceedings. In the dissertation author has compared limits and determinants of discretion in criminal proceedings. It was established that limits of discretion in criminal proceedings can be defined as a restriction of powers of subjects in criminal proceedings during the application of discretion. The scope of powers in the process of exercising discretion depends on determinants of discretion, which can be described as certain factors (features) that determine limits of discretion in particular legal situation. The essence of judicial discretion with allocation of characteristic features was established. As a specific feature of judicial discretion, it was proposed to consider its special legal significance. Unlike decisions of an investigator or prosecutor, court decisions can be used not only in these criminal proceedings, but also in other proceedings. The process of application of discretion by investigating judge during the pretrial investigation was described. It was established that in determining the amount of bail investigating judges take into account amount of property damage caused by a criminal offense, and almost do not take into account other circumstances provided by criminal procedure law. As a result, outcome of judicial discretion becomes unpredictable. The content and characteristic features of prosecutor’s discretion in criminal proceedings were revealed. It was established that one of the key features of prosecutorial discretion is the presence of departmental control. In general prosecutor is independent in his activities. However, in the structure of prosecutor’s office, in contrast to court, there is a clear hierarchy that directly or indirectly influences decisions made by prosecutor in a particular criminal proceeding using discretion. It was emphasized that such control mustn’t be considered as a violation of prosecutor’s independence, because all activities of prosecutors are built in accordance with a strict hierarchical structure. Also it was established that when granting permission to conduct investigative and covert investigative (search) actions, prosecutor, in addition to factual and legal grounds, must assess the degree of possible restriction of rights and legitimate interests of participants in criminal proceedings and the proportionality of such restriction to the expected results of the relevant proceedings. If the prosecutor concludes that the fundamental rights and freedoms of person will be significantly restricted, and the evidence to be obtained will, for example, only confirm facts that were already established, it is more appropriate to refuse in conduction of such action. Also the impact of relevant procedural actions on the further course of pre-trial investigation must be taken into account. If, for example, carrying out one investigative (search) action will make other procedural actions useless due to certain tactical features, prosecutor must take into account the value of evidence that may be obtained and, if necessary, refuse to take such action. or postpone it to a later stage of pre-trial investigation. The essence of investigator’s and detective’s discretion was determined. It was established that inner conviction of investigator and detective is not a key characteristic in the process of understanding the essence of their discretion, as it was proposed in legal doctrine. Any lawful discretion must be limited, as unlimited discretion entails the arbitrariness of the entity authorized to apply such discretion, which does not meet the criterion of legality. Also discretion may be erroneous (especially when it comes to copying one’s own behaviour or behaviour of others). Obviously, in this case, authorized subjects will also use inner conviction as a fundamental constant. But such conviction will be wrong, and law enforcer will not be able to adjust his own behaviour accordingly. It was established that effectiveness of the pre-trial investigation must be defined a feature of pre-trial investigation, which is characterized by the ability to achieve tasks of criminal proceedings provided in Art. 2 of the CPC of Ukraine, and which can be assessed number of procedural actions that were conducted, and promptness of intermediate and final procedural decisions (notification of suspicion, drafting and sending an indictment to court, closing criminal proceedings, etc.). For this purpose, head of pre-trail investigation agency must establish: 1) whether investigator (detective) cannot carry out any other procedural actions; 2) whether investigator (detective) can accelerate the ongoing procedural actions; 3) whether the investigator (detective) could avoided a situation in which he could not continue to carry out procedural actions necessary for the investigation. Factually substantiated proposals on amendments and additions to the CPC of Ukraine have been formulated in order to improve the usage of discretion in the process of investigation, consideration and resolution of criminal proceedings.
дис. ... доктора юрид. наук: 12.00.09
Торбас О.О. Розсуд у кримінальному процесі України: дис. ... д-ра юрид. наук: 12.00.09 / Торбас Олександр Олександрович. Одеса, 454 с.
Keywords: розсуд; ознаки розсуду; межі розсуду; детермінанти розсуду; суддівський розсуд; розсуд прокурора; розсуд слідчого; розсуд дізнавача; розсуд інших уповноважених суб’єктів кримінального процесу; усмотрение; признаки усмотрения; пределы усмотрения; детерминанты усмотрения; судейское усмотрение; усмотрение прокурора; усмотрение следователя; усмотрение дознавателя; усмотрение других уполномоченных субъектов уголовного процесса; discretion; features of discretion; limits of discretion; determinants of discretion; judicial discretion; prosecutor’s discretion; investigator’s discretion; detective’s discretion; discretion of other authorized subjects of criminal proceedings